The use of electrolyte leakage in the evaluation of salinity tolerance at seedling stage in maize (Zea mays L.). - Collado, Nonica Beatriz (2010)
This paper examines the use of the electrolyte leakage (Cell membrane stability) trait in the selection at seedling stage that may be important in the screen for different  mechanisms of tolerance in plants exposed to salinity.Eight accessions/lines were used five of which were populations and three inbred lines. Three seeds were planted in each pot containing perlit; these pots were put in trays with a nutrient solution. Two treatments were applied: control (cont.) where no ClNa solution was added and the other treatment receiving 100mM ClNa (salt). The experimental was carried out in controlled environmental room at 25 ºC, with 16 day length and with a relative humidity of 60%. After 14 days of each salt treatment, the seedlings were harvested. The length for shoot and radicle (SL and RL, respectively) were recorded. Shoot and radicle were separated and the samples were dried for two days until constant weight, for dry mass determination (DS and DR respectively). The cell membrane stability was estimated on the third leaf. Consequently, these traits would be extremely useful in salinity tolerance improvement programs, especially Root Length which has shown a major growth reduction compared to the controls. This apparently evidences the importance of the Root Length variable in the identification of a tolerant response. Some lines had divergent pattern to damage in membrane.